A bibliometric study of highly cited reviews in the Science Citation Index expanded™. (6th November 2013) - Ho, Yuh‐Shan; Kahn, Michael
<x xml:space="preserve">Abstract</x> Some 1, 857 highly cited reviews, namely those cited at least 1, 000 times since publication to 2011, were identified using the data hosted on the Science Citation Index Expanded™ database (Thomson Reuters, New York, NY) between 1899 and 2011. The data are disaggregated by publication date, citation counts, journals, Web of Science® (Thomson Reuters) subject areas, citation life cycles, and publications by Nobel Prize winners. Six indicators, total publications, independent publications, collaborative publications, first‐author publications, corresponding‐author publications, and single‐author publications were applied to evaluate publication of institutions and countries. Among the highly cited reviews, 33% were single‐author, 61% were single‐institution, and 83% were single‐country reviews. The United States ranked top for all 6 indicators. The G7 (United States, United Kingdom, Germany, Canada, France, Japan, and Italy) countries were the site of almost all the highly cited reviews. The top 12 most productive institutions were all located in the United States with Harvard University (Cambridge, MA) the leader. The top 3 most productive journals were Chemical Reviews, Nature, and the Annual Review of Biochemistry. In addition, the impact of the reviews was analyzed by total citations from publication to 2011, citations in 2011, and citation in publication year.